A P-silicon immersion etching solution
By using P-silica soaking corrosion liquid containing nitric acid, permonosulfuric acid, acetic acid, fluorine acid, ammonium salt and additives, the problem that traditional corrosion liquid is difficult to remove the mechanical damage layer of P-silica substrate is solved, and a uniform rough surface is achieved The generation and satisfaction of thickness requirements improve production efficiency and cost-effectiveness.
Patent Information
- Application Number
- CN202211669828.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2022-12-25
- Publication Date
- 2025-02-25
- Estimated Expiration
- 2042-12-25
AI Technical Summary
During the IGBT manufacturing process, traditional corrosion liquids are difficult to effectively remove the mechanically damaged layer of the P-silicon substrate, resulting in smooth surfaces, difficult metal ions to adhere, and easy metal layer peeling problems.
Using a P-silicon soaking corrosion solution containing nitric acid, permonosulfuric acid, acetic acid, fluorine acid, ammonium salt and additives, the oxidation capacity and surface activity of the corrosion solution are improved by optimizing the composition and proportion, and the surface roughness and thickness are ensured. Meet the requirements.
The corrosion liquid can effectively remove mechanical damage layers, generate a uniform rough surface, meet the thickness requirements of IGBT manufacturing, and improve production efficiency and cost-effectiveness.
Smart Images

Figure CN116218529B_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the cross-technical field of wet electronic chemicals and IGBT manufacturing process processing, in particular to an immersion etching solution for P-silicon. Background Art
[0002] In recent years, with the rapid development of new energy vehicles, insulated gate bipolar transistor (IGBT) power devices, as the core components of new energy vehicles, are responsible for controlling the power distribution of electric motors and matching the operation of electric motor engines, playing a pivotal role. In the manufacturing process of automotive-grade IGBTs, new challenges are faced, and the requirements for its heat dissipation efficiency, high temperature resistance, and high voltage resistance are higher. Therefore, the thickness requirements of IGBT chips are also more stringent. Before the back-gold process is performed on the bottom surface of the P-type doped collector area to form the collector, the back of the wafer that has been mechanically thinned to 150-160μm thick needs to be further chemically thinned to within 100μm to remove the mechanical damage layer left by mechanical thinning, so as to ensure the performance of the back-gold layer and avoid the back-gold peeling or cracking, which leads to excessive contact resistance and device failure. However, the traditional roughening method is to use an etching mixture of HF, HNO3, H2SO4, and water to create a rough surface. Because the viscosity of sulfuric acid is high, it will imprison the large bubbles generated during the reaction. The stationary bubbles on the surface of the wafer cause white bubble marks on the corrosion surface. Many researchers have also used an etching mixture of HF, HNO3, HAC, and water to thin the back of the wafer to remove the mechanical damage layer. However, the surface of the silicon wafer under this system is too smooth, and it is difficult for metal ions to adhere and stay on the surface. The metal layer is difficult to be tightly connected to the substrate, resulting in the metal layer peeling off.
[0003] Therefore, a P-silicon immersion etching solution is developed that can be directly used in the immersion etching process to etch away the P-silicon substrate, obtain a uniform rough surface, and meet the thickness requirements of the process. At the same time, it can also save costs and improve production efficiency. Summary of the invention
[0004] The invention provides a P-silicon immersion etching solution, which can be directly used in an immersion etching process to etch away a P-silicon substrate to obtain a uniform rough surface, meet the thickness requirements of the process, and also save costs and improve production efficiency.
[0005] The technical scheme of the invention is a P-silicon immersion etching solution, which contains nitric acid, persulfuric acid, acetic acid, fluorine-containing acid, ammonium salt, additives and deionized water.
[0006] In a preferred embodiment, the etching solution contains 36% to 40% nitric acid, 0.1% to 0.5% peroxymonosulfuric acid, 6% to 8% fluorine-containing acid, 8% to 12% acetic acid, 4% to 8% ammonium salt, 0.01% to 0.1% additives, and the remainder is deionized water.
[0007] Furthermore, the fluorine-containing acid is at least one of hydrogen fluoride, tetrafluoroboric acid, hexafluorophosphoric acid, and hexafluorosilicic acid.
[0008] More preferably, the fluorine-containing acid is hydrofluoric acid.
[0009] Further, the ammonium salt is at least one of ammonium fluoride, ammonium sulfate, ammonium acetate, ammonium persulfate, tetramethylammonium fluoride, ammonium tetrafluoroborate, ammonium hexafluorophosphate, and ammonium hexafluorosilicate;
[0010] More preferably, the ammonium salt is ammonium fluoride or ammonium acetate.
[0011] Furthermore, the additive is any one of perfluorooctanoic acid and perfluorooctane sulfonic acid.
[0012] The present invention has the following beneficial effects:
[0013] 1. In the etching solution provided by the present invention, nitric acid is used as the main oxidant, and permonosulfuric acid has strong oxidizing property due to the peroxide radical, which enhances the oxidizing ability of P-silicon, solves the problem that the energy band bending of low-B-doped silicon provides a potential barrier for holes and a potential well for electrons, and it is difficult for holes to contact the surface to participate in the reaction, thereby it is difficult to lose electrons and be oxidized, thereby shortening the initial reaction time.
[0014] 2. The acetic acid in the present invention provides an acidic environment for nitric acid, so that the oxidation potential of the solution remains stable, which plays a role in buffering the etching rate. At the same time, it also changes the bubbles generated by oxidation from large bubbles to tiny bubbles, thereby obtaining a uniform etching surface.
[0015] 3. The ammonium salt in the present invention increases the number of tiny bubbles generated during the reaction and promotes the exchange rate between the bubbles on the P-silicon wafer surface and the solution, thereby avoiding the bubble masking effect caused by the bubbles staying on the silicon wafer surface for a long time and leaving traces of bubbles remaining.
[0016] 4. The additive used in the present invention can reduce the surface tension of the solution and increase the solubility of the etching solution for the reaction products and intermediates, thereby avoiding the precipitation problem of fluorine silicon compounds and the intermediate product ammonium bifluoride during the reaction process. BRIEF DESCRIPTION OF THE DRAWINGS
[0017] Figure 1 This is the surface state of Example 1 under a high-power microscope after etching.
[0018] Figure 2 This is the surface state of Example 1 under SEM after etching.
[0019] Figure 3 This is the surface state of Example 2 under a high-power microscope after etching.
[0020] Figure 4 This is the surface state of Example 2 under SEM after etching.
[0021] Figure 5 This is the surface state of Example 3 under a high-power microscope after etching.
[0022] Figure 6 This is the surface state of Example 3 under SEM after etching.
[0023] Figure 7 This is the surface state of Example 8 under a high-power microscope after etching.
[0024] Figure 8 This is the surface state of Example 8 under SEM after etching.
[0025] Fig. 9 This is the surface state of Comparative Example 1 under a high-power microscope after etching.
[0026] Fig.10 This is the surface state of Comparative Example 1 under SEM after etching.
[0027] Fig.11 This is the surface state of Comparative Example 2 under a high-power microscope after etching.
[0028] Fig.12 This is the surface state of Comparative Example 2 under SEM after etching.
[0029] Fig.13 This is the surface state of Comparative Example 3 under a high-power microscope after etching.
[0030] Fig.14 This is the surface state of comparative example 3 under SEM after etching.
[0031] Fig.15 This is the surface state of Comparative Example 4 under a high-power microscope after etching.
[0032] Fig.16 This is the surface state of Comparative Example 4 under SEM after etching. DETAILED DESCRIPTION
[0033] The embodiments of the present invention will be described in detail below with reference to examples, but those skilled in the art will appreciate that the following examples are only used to illustrate the present invention and should not be construed as limiting the scope of the present invention.
[0034] Example 1
[0035] Embodiment 1 provides a P-silicon immersion etching solution, specifically:
[0036] The weight content of nitric acid is 38%; the weight content of permonosulfuric acid is 0.25%; the weight content of hydrofluoric acid is 7%; the weight content of acetic acid is 10%; the weight content of ammonium fluoride is 6%; the weight content of perfluorooctanoic acid is 0.05%; and the weight content of deionized water is the balance.
[0037] The above-mentioned P-silicon immersion etching solution was used to carry out an etching experiment on the mechanically polished wafer at 25°C. The etching method was immersion etching and the etching time was 10 minutes. The thickness of the silicon wafer before and after etching was detected by a spiral micrometer, and the etching rate was calculated. The etching rate = (H1-H2) / t. The Roughness of the surface after etching was detected by a surface roughness meter, Ra, and the surface effect after etching was observed using a high-power microscope and SEM.
[0038] Wherein, H1 is the thickness of the silicon wafer before the reaction, H2 is the thickness of the silicon wafer after the reaction, t is the reaction time, and Ra is the surface roughness after the reaction. The etching rate and etching effect are recorded in Table 1. The surface state after etching is shown in Table 1. Figure 1 , Figure 2 As shown, the etching reaction is complete, unit cells of uniform size are generated, a uniform frosted surface is obtained, and an ideal roughening effect is achieved.
[0039] Example 2
[0040] Embodiment 2 provides a P-silicon immersion etching solution, specifically:
[0041] The weight content of nitric acid is 42%; the weight content of permonosulfuric acid is 0.25%; the weight content of hydrofluoric acid is 6%; the weight content of acetic acid is 21%; the weight content of ammonium fluoride is 4%; the weight content of perfluorooctanoic acid is 0.01%; and the weight content of deionized water is the balance.
[0042] The experimental method is the same as in Example 1, and the etching rate and etching effect are recorded in Table 1. The surface state after etching is as follows Figure 3 , Figure 4 As shown, the surface is smooth and mirror-like with low roughness, which cannot meet the requirements of the back-gold process.
[0043] Example 3
[0044] Embodiment 3 provides a P-silicon immersion etching solution, specifically:
[0045] The weight content of nitric acid is 38%; the weight content of hydrofluoric acid is 6%; the weight content of acetic acid is 12%; the weight content of ammonium fluoride is 5%; the weight content of perfluorooctanoic acid is 0.05%; and the weight content of deionized water is the balance.
[0046] The experimental method is the same as in Example 1, and the etching rate and etching effect are recorded in Table 1. The surface state after etching is as follows Figure 5 , Figure 6 As shown, the reaction is incomplete, resulting in black dot-like color differences on the surface.
[0047] Example 4
[0048] Embodiment 4 provides a P-silicon immersion etching solution, specifically:
[0049] The weight content of nitric acid is 38%; the weight content of permonosulfuric acid is 0.25%; the weight content of hydrofluoric acid is 6%; the weight content of acetic acid is 18%; the weight content of ammonium fluoride is 6%; and the weight content of deionized water is the balance.
[0050] The experimental method is the same as that of Example 1, and the etching rate and etching effect are recorded in Table 1. In addition, white insoluble matter appears during the etching process, and the solution becomes turbid.
[0051] Example 5
[0052] Embodiment 5 provides a P-silicon immersion etching solution, specifically:
[0053] The weight content of nitric acid is 35%; the weight content of permonosulfuric acid is 0.25%; the weight content of hydrofluoric acid is 8%; the weight content of acetic acid is 12%; the weight content of ammonium fluoride is 8%; the weight content of perfluorooctanoic acid is 0.05%; and the weight content of deionized water is the balance.
[0054] The experimental method is the same as that of Example 1, and the etching rate and etching effect are recorded in Table 1. The surface state after etching is similar to that of Comparative Example 3.
[0055] Example 6
[0056] Embodiment 6 provides a P-silicon immersion etching solution, specifically:
[0057] The weight content of nitric acid is 38%; the weight content of permonosulfuric acid is 0.25%; the weight content of hydrofluoric acid is 10%; the weight content of acetic acid is 12%; the weight content of ammonium fluoride is 5%; the weight content of perfluorooctanoic acid is 0.05%; and the weight content of deionized water is the balance.
[0058] The experimental method is the same as that of Example 1, and the etching rate and etching effect are recorded in Table 1. The etching rate is too fast, and it is difficult to control the stress removal thickness of 50-60 μm.
[0059] Example 7
[0060] Embodiment 7 provides a P-silicon immersion etching solution, specifically:
[0061] The weight content of nitric acid is 38%; the weight content of permonosulfuric acid is 0.25%; the weight content of hydrofluoric acid is 7%; the weight content of acetic acid is 4%; the weight content of ammonium fluoride is 5%; the weight content of perfluorooctanoic acid is 0.05%; and the weight content of deionized water is the balance.
[0062] The experimental method is the same as that of Example 1, and the etching rate and etching effect are recorded in Table 1. The etching reaction is slow and wear lines still exist.
[0063] Example 8
[0064] Embodiment 8 provides a P-silicon immersion etching solution, specifically:
[0065] The weight content of nitric acid is 38%; the weight content of permonosulfuric acid is 0.25%; the weight content of hydrofluoric acid is 8%; the weight content of acetic acid is 18%; the weight content of perfluorooctanoic acid is 0.05%; and the weight content of deionized water is the balance.
[0066] The experimental method is the same as in Example 1, and the etching rate and etching effect are recorded in Table 1. The surface state after etching is as follows Figure 7 , Figure 8 As shown, although a large number of tiny bubbles appear and are quickly exchanged between the test piece and the solution during the etching process, there are traces of bubble flow on the surface after etching.
[0067] Example 9
[0068] Embodiment 9 provides a P-silicon immersion etching solution, specifically:
[0069] The weight content of nitric acid is 38%; the weight content of permonosulfuric acid is 0.25%; the weight content of hydrofluoric acid is 8%; the weight content of acetic acid is 10%; the weight content of ammonium fluoride is 5%; the weight content of perfluorooctanoic acid is 0.15%; and the weight content of deionized water is the balance.
[0070] The experimental method is the same as that of Example 1, and the etching rate and etching effect are recorded in Table 1. There are many bubbles in the etching solution, and during the etching process, large bubbles also adhere to the surface, forming a masking effect, resulting in incomplete surface reaction, and only some parts react, and its surface state is similar to that of Comparative Example 1.
[0071] Example 10
[0072] Embodiment 10 provides a P-silicon immersion etching solution, specifically:
[0073] The weight content of nitric acid is 38%; the weight content of permonosulfuric acid is 0.25%; the weight content of hydrofluoric acid is 8%; the weight content of acetic acid is 10%; the weight content of ammonium acetate is 5%; the weight content of perfluorooctanoic acid is 0.05%; and the weight content of deionized water is the balance.
[0074] The experimental method is the same as that of Example 1, and the etching rate and etching effect are recorded in Table 1. The etching effect is similar to that of Example 1.
[0075] Comparative Example 1:
[0076] Comparative Example 1 provides a P-silicon immersion etching solution, specifically:
[0077] The weight content of nitric acid is 7%; the weight content of sulfuric acid is 80%; the weight content of hydrofluoric acid is 3%; and the weight content of deionized water is the balance.
[0078] The experimental method is the same as in Example 1, and the etching rate and etching effect are recorded in Table 1. The surface state after etching is as follows Fig. 9 , Fig.10 As shown in the figure, there are large bubbles attached to the surface of the silicon wafer, forming bubble traces.
[0079] Comparative Example 2
[0080] Comparative Example 2 provides a P-silicon immersion etching solution, specifically:
[0081] The weight content of nitric acid is 24%; the weight content of sulfuric acid is 60%; the weight content of hydrofluoric acid is 3%; and the weight content of deionized water is the balance.
[0082] The experimental method is the same as in Example 1, and the etching rate and etching effect are recorded in Table 1. The surface state after etching is as follows Fig.11 , Fig.12 As shown in the figure, the surface after etching is white and mirror-like, with corrosion pits visible to the naked eye.
[0083] Comparative Example 3
[0084] Comparative Example 3 provides a P-silicon immersion etching solution, specifically:
[0085] The weight content of nitric acid is 24%; the weight content of hydrofluoric acid is 8%; the weight content of acetic acid is 50%; and the weight content of deionized water is the balance.
[0086] The experimental method is the same as in Example 1, and the etching rate and etching effect are recorded in Table 1. The surface state after etching is as follows Fig.13 , Fig.14 As shown. Almost no reaction, unable to remove mechanically damaged layer.
[0087] Comparative Example 4
[0088] Comparative Example 4 provides a P-silicon immersion etching solution, specifically:
[0089] The weight content of nitric acid is 30%; the weight content of hydrofluoric acid is 8%; the weight content of acetic acid is 18%; the weight content of ammonium fluoride is 10%, and the weight content of deionized water is the balance.
[0090] The experimental method is the same as in Example 1, and the etching rate and etching effect are recorded in Table 1. The surface state after etching is as follows Fig.15 , Fig.16 As shown. The reaction produced colorful porous silicon, which could not meet the demand.
[0091] Table 1 Etching rates and experimental results of etching experiments performed in Examples 1 to 10 and Comparative Examples 1 to 4.
[0092]
[0093]
[0094] The above embodiments and comparative examples are only examples for clear demonstration, and are not limited to the above embodiments. For those skilled in the art, the above embodiments have many variations or combinations, and it is not necessary and impossible to cite all the embodiments here. Therefore, the changes or modifications based on the above embodiments are still within the protection scope of the present invention.
Claims
1. A P-silicon immersion etching solution, characterized in that: In terms of weight percentage, the nitric acid content in the etching solution is 36% to 40%; the persulfuric acid content is 0.1% to 0.5%; the fluorine-containing acid content is 6% to 8%; the acetic acid content is 8% to 12%; the ammonium salt content is 4% to 8%; the additive content is 0.01% to 0.1%; the balance is deionized water, and the fluorine-containing acid is hydrofluoric acid; The ammonium salt is ammonium fluoride or ammonium acetate; The additive is perfluorooctanoic acid.
Citation Information
Patent Citations
Etching-solution composition and wet etching method using same
CN104039925A
Silicon chip grinding liquid
CN109913222A